Presentation and management of hypoparathyroidism in a paediatric patient - a case report - Ateeque, Kanza; Fatima, Warisha; Rehman, Iqra; Jamal, Maira (Journal of the Pakistan Medical Association, 2023)
Hypoparathyroidism occurs due to insufficient parathyroid gland activity leading to abnormal calcium and phosphate levels. The presentation of hypoparathyroidism is rare in adults and mostly encountered in the paediatric population. We present a case of a 3.5-month-old male infant with the presenting complaint of an episode of afebrile generalized tonic-clonic seizure. Haematological, urinary, cerebro-spinal fluid and radiological investigations were unremarkable but a biochemical profile revealed hypocalcaemia, hyperphosphataemia and lowered vitamin D3 levels. Parathyroid hormone profile showed a decreased level, confirming diagnosis of hypoparathyroidism. Intravenous administration of calcium and magnesium in combination with oral activated vitamin D3 and phosphate binders managed to resolve symptoms and maintain normal levels. The rationale of this case is to confirm the necessity of early diagnosis to prevent irreversible sequelae of hypocalcaemia and regular monitoring of treatment to avoid side-effects of medication. Keywords: Child, preschool, Hypocalcaemia, Hyperphosphataemia, Hypoparathyroidism, Seizures